Evaluasi Penerapan Sistem Remunerasi dan Peningkatan Produktivitas Tenaga Kerja Pelayanan (Studi pada RSUD Dr. H. Abdul Moeloek) - Dina Puspa Sari (Master in Accounting Program, 2017)
Remuneration is a financial reward received by employees in return for their contribution to the organization and is expressed as direct or indirect return. Remuneration can encourage motivation and increase employee-s’ productivity. This is also in the hospital as a capital-intensive, human resource-intensive as well as knowledge and technology-intensive health care institution. In the hospital, the service workforce includes doctors and nurses as the core of human resources and the organization-’s revenue center. Guidelines for a good preparation of remuneration system in Indonesian health care institutions are regulated in the Minister of Health’s Regulation No. 18 of 2014. Based on that regulation, effective remuneration must meet principles of fairness; principles of appropriateness; principles of accuracy; policy; performance evaluation; and control over the remuneration. A remuneration that fulfills all those elements will encourage motivation and increase employee-’s productivity. This research was conducted at Dr. H. Abdul Moeloek General Hospital, it was qualitative research which used a case study approach. Data collection techniques used were interviews, observations, questionnaires, and documentations. The interview were conducted on 6 respondents.The questionnaires were given to 47 respondents which consisted of doctors and nurses. The questionnaires were analyzed using descriptive statistics by calculating the mean values. The result of this research showed that the implementation of remuneration system at Dr. H. Abdul Moeloek General Hospital has not been effective. The implementation of the remuneration system has not fulfilled the principle of fairness, principle of appropriateness, principle of accuracy, policy, performance evaluation, and control. Dr. H. Abdul Moeloek General Hospital is expected to improve its remuneration system so that the real purpose of remuneration can be fulfilled, that is, to encourage motivation and to increase employee-s’ productivity that way remuneration can be considered effective.